PEMANFAATAN TEKNOLOGI INFORMASI DENGAN BAIK DALAM RANGKA MENCEGAH BULLYING DI TBM PUSTAKA PRIMA - Candra Juliansyah, Syafana; Dwi Andika, Muhamad Rizki; Rachmadika, Fasha; Rahmayanti, Adisti Aisyah; Salsabila Nurasa, Dwi Mayovi; Dara, Fayla Lakmi (Jurnal Pengabdian Masyarakat Indonesia, 2024)
This article discusses the utilization of information technology to prevent bullying in TBM Pustaka Prima, a community-based library in Tasikmalaya, West Java. The authors conducted a community service program that aimed to educate the library staff and visitors, especially teenagers, about the dangers and impacts of bullying, both offline and online. The program also provided guidance on how to use information technology wisely and responsibly, such as avoiding cyberbullying, protecting personal data, and accessing reliable sources of information. The program consisted of several activities, such as seminars, workshops, counseling, and mentoring. The results showed that the program increased the awareness and knowledge of the participants about bullying and information technology, as well as improved their skills and attitudes in using information technology. The authors suggest that similar programs should be implemented in other community-based libraries to promote a safe and positive environment for learning and socializing.